Rectal duplication associated with rectoperineal fistula: A case report - Noah Brown; Robert Swendiman; Douglas Barnhart; Scott Short; Michael Rollins (Elsevier, 2023)
Introduction: Rectal duplication is a rare condition with less than 100 cases documented in the literature. There are eleven reported cases of rectal duplication and anorectal malformation occurring concurrently. We present one such case with intraoperative discovery of the duplication and discuss intraoperative techniques and postoperative management. Case Presentation: A term male was transferred to our institution with an anorectal malformation noted on exam. Routine prenatal imaging had revealed an absent right kidney without any other anatomic abnormalities noted. Physical exam revealed a perineal fistula anterior to the sphincter complex. The patient was initially managed with twice daily dilations of the fistula until 2 months of life. He was then taken to the operating room for planned posterior sagittal anorectoplasty (PSARP). Intraoperatively, a blind ending tubular duplication was discovered anterior to the true rectum. This was managed with creation of a common channel and tapering rectoplasty followed by completion of the anoplasty. A diverting loop ileostomy was performed. Prior to ileostomy closure at 6 months of life, a contrast enema was performed and demonstrated that the duplication extended to the level of the splenic flexure. A Tc99 scan was obtained to rule out ectopic gastric mucosa. Conclusion: This case illustrates a rare presentation and operative management of a colon and rectal duplication associated with an anorectal malformation and emphasizes the importance of adequate mobilization of the rectal fistula when performing a PSARP. Level Of Evidence: Level V